2003
DOI: 10.1007/s00122-003-1365-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional genetic differentiation in Western Australian sandalwood (Santalum spicatum) as revealed by nuclear RFLP analysis

Abstract: Western Australian sandalwood, Santalum spicatum, is widespread in the semi-arid and arid regions of Western Australia, and there is some morphological variation suggestive of two ecotypes. The level and structuring of genetic diversity within the species was investigated using anonymous nuclear RFLP loci. Santalum spicatum showed moderate levels of genetic diversity compared to other Australian tree species. The northern populations in the arid region showed greater levels of diversity and less population dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 16 publications
(17 reference statements)
7
79
0
3
Order By: Relevance
“…Significant structuring of the diversity occurs with two main clades that are geographically separated, one centred on the southern region and one centred in the north of the distribution. This differentiation of two lineages is consistent with the identification of differences between the regions in the influence of genetic processes on the nuclear genome (Byrne et al, 2003). It is also consistent with the identification of two ecotypes in these regions, based on morphological variation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Significant structuring of the diversity occurs with two main clades that are geographically separated, one centred on the southern region and one centred in the north of the distribution. This differentiation of two lineages is consistent with the identification of differences between the regions in the influence of genetic processes on the nuclear genome (Byrne et al, 2003). It is also consistent with the identification of two ecotypes in these regions, based on morphological variation.…”
Section: Discussionsupporting
confidence: 88%
“…The genetic patterns in the nuclear and chloroplast genomes both suggest that the southern populations have been established more recently than the northern populations. However, the nuclear genome showed greater differentiation in southern populations (southern y ¼ 0.108, northern y ¼ 0.055; Byrne et al, 2003), whereas the chloroplast genome identified greater differentiation in the northern populations (northern G ST ¼ 95%, southern G ST ¼ 81%). This suggests that the lower differentiation in the chloroplast genome is not likely to be a result of population sampling, higher seed dispersal or greater abundance, but may be due to less time for fragmentation to influence divergence.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, this information is rarely available for either flora or fauna in any ecosystem. South-western Australia is known for its extreme diversity of plants and highly threatened ecosystems, but there are comparatively few datasets analysing genetic differentiation within species that might lead to an understanding of processes generating that diversity (but for plants see Coates and Hamley 1999;Byrne and Macdonald 2000;Byrne et al 2003aByrne et al , 2003bCoates et al 2003;Broadhurst et al 2004;Byrne and Hines 2004;Wheeler and Byrne 2006; and for animals see Driscoll 1998asee Driscoll , 1998bReid 2002;Munasinghe et al 2004;Gouws et al 2006;Edwards 2007a;2007b;Edwards et al 2007Edwards et al , 2008. Genetic data documenting variation within species can be used for conservation management in two ways: (1) to assess common patterns of variation that reflect historical events such as climate shifts, patterns of isolation or tectonic activity that might define the spatial array of genetic diversity and inform management actions (e.g.…”
Section: Introductionmentioning
confidence: 99%